Monitoring the slope movement of the Shuping landslide in the Three Gorges Reservoir of China, using X-band time series SAR interferometry. Issue 12 (15th June 2016) - Liu, Guang; Guo, Huadong; Perski, Zbigniew; Fan, Jinghui; Bai, Shibiao; Yan, Shiyong; Song, Rui
Abstract: As the largest water conservation project in China, the Three Gorges Reservoir has attracted a lot of attention. However, the rise in water level due to the dam operation has caused many ecological problems. Since the impoundment of the Three Gorges Reservoir in the year 2003, many landslides have taken place. The Shuping landslide is a reactivated landslide and has been continuously moving since the impoundment. It has resulted in serious dangers to local residence and the role of the Yangtze River as an inland waterway. Spaceborne Synthetic Aperture Radar (SAR) sensors obtain images periodically and regionally, from which the characteristics of the slope movement could be obtained timely and cost effectively. In this study, an adapted time series InSAR technique considering SRTM bias is proposed and used to process TerraSAR-X strip map images with 3 meters resolution which collected in the first quarter of 2012. Compared with previous studies with low resolution SAR data, our results obtain much more stable points and reveal the movement pattern of the active slope of Shuping landslide in detail, and they show that there are two main landslide bodies obviously; one is located in the eastern part of the landslide, while the other is located in the western part of the landslide, the movement velocity is up to 40 mm month −1, and the results are well-consistent with the in situ results. Furthermore the active movement boundaries was identified through analysing the time series InSAR results, the shape of the landslide is chair-like, and the boundaries lie mostly along ditches. The results show that more details about the landslide could be revealed using the proposed time series InSAR method and high resolution TerraSAR-X SAR data, and this provide a more comprehensive way for landslide movement monitoring, which will be useful for landslide management.